2017
DOI: 10.1039/c7ob00998d
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled artificial viral capsids bearing coiled-coils at the surface

Abstract: In order to construct artificial viral capsids bearing complementary dimeric coiled-coils on the surface, a β-annulus peptide bearing a coiled-coil forming sequence at the C-terminus (β-annulus-coiled-coil-B) was synthesized by a native chemical ligation of a β-annulus-SBn peptide with a Cys-containing coiled-coil-B peptide. Dynamic light scattering (DLS) measurements and transmission electron microscopy (TEM) images revealed that the β-annulus-coiled-coil-B peptide self-assembled into spherical structures of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Among them, helical hetero-dimers have wide applications in the design of three-dimensional (3D) nanostructures. For example, complementary dimeric coiled-coil peptides can induce the self-assembly of artificial viral capsids 40,41. Protein–protein helical hetero-dimers were used in colloidal assembly of polystyrene microparticles42 and protein super-structures 43.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, helical hetero-dimers have wide applications in the design of three-dimensional (3D) nanostructures. For example, complementary dimeric coiled-coil peptides can induce the self-assembly of artificial viral capsids 40,41. Protein–protein helical hetero-dimers were used in colloidal assembly of polystyrene microparticles42 and protein super-structures 43.…”
Section: Introductionmentioning
confidence: 99%
“…CD analysis has shown that both the mammalian and bacterial expressed proteins are structurally stable, although the molar ellipticity per residue for the bacterial express protein is lower compared to the M1-2x and M2-3x proteins. It is to be noted that both M1-2x and M2-3x have the tGCN4 tetramerization domain that forms highly coiled-coil leucine zipper, tetramer structure that is rich in alpha-helix that significantly contributed for the high molar ellipticity in the tGCN4 tagged proteins and the spectra generated might be coming from the tGCN4 domains (67).…”
Section: Discussionmentioning
confidence: 99%
“…Typically, assembly motifs that are effective for the display of high molecular weight functional motifs are also folded proteins such as those that comprise viral capsids. [203,204] The resulting supramolecular structures thus tend to be three-dimensional capsids or particles that maximize the spatial separation of the large displayed cargo. For example, Matsuura et al [67] have engineered a system that displays human serum albumin (HSA) on a viral capsid mimetic ( Figure 3).…”
Section: Assembly Motif Display Motif Section Referencesmentioning
confidence: 99%